A novel CMAS‐resistant material based on thermodynamic equilibrium design: Apatite‐type Gd10(SiO4)6O3. Issue 5 (24th January 2020) - Wu, Di; Zhang, Han; Shan, Xiao; Yang, Fan; Guo, Fangwei; Zhao, Xiaofeng; Xiao, Ping; Gong, Shengkai
Abstract: Calcium‐magnesium‐alumino‐silicates (CMAS) melt attack has been a critical issue for the thermal barrier coatings (TBCs) with ever‐increasing engine operating temperature. In this study, a novel CMAS‐resistant material apatite‐type Gd10 (SiO4 )6 O3 is developed for TBCs application based on thermodynamic equilibrium design. The chemical reaction of Gd10 (SiO4 )6 O3 bulk and CMAS melt is investigated at 1300°C. The CMAS corrosion resistance of Gd10 (SiO4 )6 O3 bulk is evaluated and compared with the well‐studied CMAS‐resistant material Gd2 Zr2 O7 (GZO). It is found that Gd10 (SiO4 )6 O3 shows a significantly enhanced CMAS resistance, including lower intrinsic CMAS infiltration rate (~1.09 μm/h 1/2 ) and smaller infiltration upper limit (50‐62 μm) for a 20 mg/cm 2 CMAS deposition. More importantly, for Gd10 (SiO4 )6 O3, the CMAS infiltration only alters the composition but does not change the crystal structure or destroy microstructural integrity. The reaction mechanism is elucidated as following two stages: (a) surface Gd10 (SiO4 )6 O3 quickly transforms into Ca2 Gd8 (SiO4 )6 O2 in suit by interdiffusion with CMAS melt and then is thermodynamically stable with CMAS melt, thereby effectively inhibiting the further CMAS infiltration and (b) with the ongoing interdiffusion of Gd/Ca, the CMAS‐infiltrated layer slowly thickens and follows a parabolic law. Meanwhile, the CMAS melt gradually precipitates Ca2 Gd8 (SiO4 )6 O2 and CaAl2 Si2 O8 (anorthite) until the melt is exhausted.